Genetic variation in malaysian cymbopogon citratus (lemongrass) based on inter simple sequence repeat (ISSR) marker - Wan Mohd Jaafar, Wan Nurfatin (2015)
This research was to investigate the genetic variation among Cymbopogon citratus sp. or commonly known as lemongrass in Malaysia. A total of 39 C. citratus were obtained from across Malaysia. Using the CTAB extraction method, DNA was extracted from the 39 samples and inter simple sequence repeat (ISSR) markers were used to estimate their genetic variation. Out of 25 ISSR primers tested, only seven ISSR primers were chosen based on their ability to amplify DNA fragments that were easy to score on an agarose gel and reproducible. In total 70 loci were identified and 59 were found to be polymorphic with an average of 8.43 polymorphic loci per primer. Using the POPGENE program values of Shannon index was calculated to estimate the genetic diversity of C. citratus and the highest values obtained is 0.2263 which indicate low level of genetic diversity. Genetic distances were also calculated using the GenAlEx program and the average for the genetic distance of all samples is 16.35. From the data obtained, a phylogenetic tree was constructed using the UPGMA method. Three cluster were generated, where 2 cluster share the same branch, and the third cluster in the second branch.